Transforming diagnosis through artificial intelligence - Luciana D’Adderio; David W. Bates (npj Digital Medicine)
Artificial intelligence (AI) is increasingly permeating the fabric of medicine, but getting full benefits will likely require fundamental changes in practice. Accepting this will be challenging for many clinicians. However, it may be necessary to ensure that AI’s ambitious promises translate into real-life improvement.